Portable-health monitoring of oxygen saturation and pulse on udoo device [electronic resource] - Wan Muhammadhafiz Wan Ibrahim, 1992- , author; Mohamad Kamal Abd. Rahim, supervisor (2015)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Elektronik)) - Universiti Teknologi Malaysia, 2015